Visual Perception of Differently Shaped and Colored Stimuli - Yu A Chudina; D A Shlyakhta (Peoples' Friendship University of Russia (RUDN University), 2014)
The results of the experimental research of visual perception of differently shaped and colored stimuli have been described in the article. The main goal of the experiment was to identify a combination of visual modules, employed in recognizing the stimuli. The desired aim was achieved by building a spherical model of the stimuli and interpreting its formal and contensive properties in terms of vector approach. It has been observed that recognizing complex stimuli is realized as a multichannel network with a specific combination of graphic and color two-channel modules, modeled in the form of a multidimentional sphere.